Mathematical simulation of brushless double stator axial flux magnetoelectric generator for small power electric complexes - Chumak, Vadim Vladimirovich; Kovalenko, Mykhaylo; Kovalenko, Iryna Yakivna; Tkachuk, Ihor; Tymoshchuk, Oksana (Національний технічний університет "Харківський політехнічний інститут", 2023)
This paper presents the design of a magneto-electric generator with an axial magnetic flux (MEGAP) and a double stator, which is used for an autonomous wind-electric complex. Contactless MEGAPs have the advantages of permanent magnet generators: high reliability, efficiency; and generators with electro magnetic excitation: the possibility of adjusting the output parameters (voltage, power) using an additional excitation winding. In order to meet the require ments of a stand-alone multiplier-less wind power plant, a MEGAP structure consisting of a double stator and a single rotor has been investigated. The use of a double stator design allows more efficient use of the active volume of the generator, increasing its power and stabilizing the output voltage of the stator winding. A three-dimensional numerical field mathematical model of MEGAP was developed. The model fully takes into account the design features of the generator under study, namely the presence of an axial flow from the stator winding and the flow generated by the additional winding. With the help of the model, the external characteristics were calculated, which indicates the correspondence of the developed mathematical model to physical processes. The analysis of magnetic induction in the air gap and in other structural elements of the generator under study was carried out. The analysis of the obtained values showed that the geometric dimensions of the generator, which were previously selected, are correct and do not require significant adjustments. In the future, it allows you to use the results of this calculation for the preparation of documentation for the production of the prototype. Static characteristics of MEGAP and values of magnetic parameters in all structural elements were studied. An additional winding is used to stabilize the output voltage when the speed of rotation of the generator changes and at different loads. At a relative power of the additional winding of ≈7%, the output voltage of the generator increases by ≈24%. A more significant result can be achieved by adjusting the current of the additional winding with special controllers.

В даній роботі представлена конструкція магнітоелектричного генератора з аксіальним магнітним потоком (МЕГАП) та подвійним статором, який використовується для автономного вітроелектричного комплексу. Безконтактні МЕГАП мають переваги генераторів на постійних магнітах: висока надійність, ефективність; і генератори з електромагнітним збудженням: можливість регулювання вихідних параметрів (напруга, потужність) за допомогою додаткової обмотки збудження. Щоб задовольнити вимоги до автономної безмультиплікаторної вітроелектричної установки, досліджено структуру МЕГАП, що складається з подвійного статора та одного ротора. Використання конструкції подвійного ста тора дозволяє більш ефективно використовувати активний об'єм генератора, підвищити його потужність і стабілізувати вихідну напругу обмотки статора. Розроблено тривимірну чисельну польову математичну модель МЕГАП. Модель повністю враховує особливості конструкції досліджуваного генератора, а саме наявність осьового потоку від обмотки статора та потоку, що утворюється додатковою обмоткою. За допомогою моделі розрахована зовнішня характеристика, що свідчить про відповідність розробленої математичної моделі фізичним процесам. Проведено аналіз магнітної індукції в повітряному проміжку та в інших конструкційних елементах досліджуваного генератора. Аналіз отриманих величин показав, що геометричні розміри генератора, що були вибрані попередньо коректні і не потребують суттєвих коригувань. В подальшому, це дозволяє використовувати результати даного розрахунку для підготовки документації по виготовленню прототипу. Досліджено статичні характеристики МЕГАП та значення магнітних параметрів у всіх елементах конструкції. Додаткова обмотка використовується для стабілізації вихідної напруги при зміні швидкості обертання генератора і при різному навантаженні. При відносній потужності додаткової обмотки ≈7% вихідна напруга генератора зростає на ≈24%. Більш значного результату можна досягти, регулюючи струм додаткової обмотки спеціальними контролерами.
Математичне моделювання безконтактного аксіального магнітоелектричного генератора із подвійним статором для електричних комплексів малої потужності
Keywords: axial flux magnetoelectric generator; double stator; mathematical simulation; axisymmetric model; генератор з аксіальним магнітним потоком; подвійний статор; математичне моделювання; асиметрична модель